From big bang to big data a history of the media - Jarlbrink, Johan 1978-; Lundell, Patrik 1969-; Snickars, Pelle 1971- (McGill-Queen’s University Press, 2023)
"Does media history really start with a bang? More than just newspapers, television, and social networks, media are best understood as the means by which any information is communicated, from cosmic radiation traces to medieval church bells to modern identity documents. Cultures are held together as much by bookkeeping and records as they are by stories and myths. From Big Bang to Big Data is a long history of the media--how it has been established, used, and transformed from the beginning of recorded time until the present. It is not primarily a story of revolutions and innovations, but of continuities and overlaps that reveal surprising patterns across history. Many media were invented as ways to store and share information, and many have served as powerful tools for administration and control. The concerns raised about media today, whether about privacy, piracy, or anxieties over declining cultural standards, preoccupied earlier generations too. In a playful style, accompanied by more than one hundred illustrations, the authors show us how every society has been a media society in its own way. From antique graffiti to last year’s viral YouTube clip, the past is only approachable through media. From Big Bang to Big Data provides a new way of thinking about media in history--and about human societies past and present."--
Keywords: Geschichte; Kommunikation; Medien; Mass media / History; Mass media; History